Sensitive methane detection based on quartz-enhanced photoacoustic spectroscopy with a high-power diode laser and wavelet filtering. (September 2020) - Li, Yu; Wang, Ruozhu; Tittel, Frank K.; Ma, Yufei
Highlights: A high power diode laser was used as excitation source for CH4 detection. 30.72 kHz quartz tuning fork was used as an acoustic wave transducer. A micro-resonator and water vapor were added to enhance the signal level. Wavelet filtering was adopted to improve the SNR of the CH4 -QEPAS sensor. Abstract: Quartz-enhanced photoacoustic spectroscopy (QEPAS) based methane (CH4 ) detection using a high power continuous wave (CW), single mode diode laser with an emission wavelength at 2.3 μm was demonstrated. A diode laser with a high output power of 6.3 mW and a quartz tuning fork (QTF) with a low resonant frequency of 30.72 kHz were used to improve the CH4 -QEPAS sensor performance. A micro-resonator and water vapor acted as a catalyst for improving the relaxation rate of the target gas molecule were added in the CH4 -QEPAS sensor for further enhancing the signal level. A minimum detection limit (MDL) of such a CH4 -QEPAS sensor reached 7.9 parts per million (ppm). After utilizing wavelet filtering, the signal-to-noise ratio (SNR) was improved by a factor of 3.6 and a lower MDL of 2.2 ppm was achieved. In order to evaluate the long-term stability of such a CH4 -QEPAS sensor an Allan deviation analysis was implemented.